2009
DOI: 10.2337/db09-0216
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Exosome-Like Vesicles Mediate Activation of Macrophage-Induced Insulin Resistance

Abstract: OBJECTIVEWe sought to determine whether exosome-like vesicles (ELVs) released from adipose tissue play a role in activation of macrophages and subsequent development of insulin resistance in a mouse model.RESEARCH DESIGN AND METHODSELVs released from adipose tissue were purified by sucrose gradient centrifugation and labeled with green fluorescent dye and then intravenously injected into B6 ob/ob mice (obese model) or B6 mice fed a high-fat diet. The effects of injected ELVs on the activation of macrophages we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
443
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 452 publications
(466 citation statements)
references
References 48 publications
13
443
2
8
Order By: Relevance
“…These results suggest that exosomes derived from obese mice promote activation of macrophages. Previously, Deng et al (2009) reported that injection of exosomes isolated from culture supernatant of visceral adipose tissues excited from ob/ob mice led to increase in IL-6 and TNF-α levels and induce insulin resistance in recipient mice (Deng et al, 2009) In conclusion, the present study showed that serum adiponectin is partially associated with exosomes in mice. Considering that adiponectin is produced exclusively by adipocytes, adiponectin associated exosomes in serum could be derived from adipocytes.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…These results suggest that exosomes derived from obese mice promote activation of macrophages. Previously, Deng et al (2009) reported that injection of exosomes isolated from culture supernatant of visceral adipose tissues excited from ob/ob mice led to increase in IL-6 and TNF-α levels and induce insulin resistance in recipient mice (Deng et al, 2009) In conclusion, the present study showed that serum adiponectin is partially associated with exosomes in mice. Considering that adiponectin is produced exclusively by adipocytes, adiponectin associated exosomes in serum could be derived from adipocytes.…”
Section: Resultssupporting
confidence: 58%
“…In fact, previous in vitro studies have demonstrated that mouse exosomes are associated with adiponectin. Deng et al and Sano et al respectively identified adiponectin by proteomic analysis in the exosomes released from cultured mouse adipose tissue and mouse adipocyte cell line 3T3-L1 (Deng et al, 2009;Sano et al, 2014). Given that adiponectin is produced exclusively by adipocytes, and considering that cultured adipose tissue and 3T3-L1 adipocytes release exosomes (Deng et al, 2009;Sano et al, 2014), it is possible that adiponectin-associated exosomes in serum are derived from adipocytes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations